Day 2 Wed, March 27, 2019 2019
DOI: 10.2523/iptc-19396-ms
|View full text |Cite
|
Sign up to set email alerts
|

Separator Pressure Optimisation and Cost Evaluation of a Multistage Production Unit Using Genetic Algorithm

Abstract: Once reservoir fluid is brought to the surface it is separated to discrete streams of oil and gas in production unit. This should be conducted with consideration of maximizing oil production and to decreasing total costs as well. The regulation of separators pressure is a key point to achieve the highest oil recovery in this process. In addition, estimating the optimum number of separation stages, would augment the design of production plant economically. Adjusting separator pressure is usually conducted by em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In refs. [2,7,9,45] an improvement in terms of increased liquid production is explicitly stated compared to a non-optimized liquid production. The improvement observed in the present study is estimated using the difference between the base case and optimized profit cf.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In refs. [2,7,9,45] an improvement in terms of increased liquid production is explicitly stated compared to a non-optimized liquid production. The improvement observed in the present study is estimated using the difference between the base case and optimized profit cf.…”
Section: Resultsmentioning
confidence: 99%
“…By optimizing the pressure in the first three separators, it was found that the oil production could be increased by approximately 2% and 8%, for crude and gas condensate, respectively. Motie et al [9] made a comprehensive study investigating the optimum separator pressure in a multistage separation train, studying the effect of the number of stages, both in terms of operating conditions, but also in terms of an NPV analysis in order to investigate to which extent the added cost of additional equipment for additional separation stages can be justified. The optimization of separator pressures was carried out by means of a genetic algorithm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2% and 8%, for crude and gas condensate, respectively. Motie et al [9] made a comprehensive study investigating the optimum separator pressure in a multistage separation train, studying the effect of the number of stages, both in terms of operating conditions, but also in terms of an NPV analysis in order to investigate to which extent the added cost of additional equipment for additional separation stages can be justified. The optimization of separator pressures was carried out by means of a genetic algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Common for refs. [2][3][4][5][6][7][8][9] is the lack of a compression system providing condensate recycle streams i.e. these studies assume a simple straight through process with the number of controllable variables normally not exceeding 2 to 5.…”
Section: Introductionmentioning
confidence: 99%